KONSEP PENARI DAN DESAIN RUANG PADA TARI MERENUNGKU ADALAH GERAK - Rochayati, Rully (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The writing is titled Concept of Dancers and Spatial Design on Dancing My Dream Is Motion. A writing that contains about the study of a work of dance that is discussed from the perspective of the study of the concept of dancers and spatial design. the whole work of dance is discussed in the concept of dancers by dividing the subject among other aspects of the number of dancers, sex and posture aspects, aspects of the unity of the composition of the group again termed the facet of the direction of the dancer, the "distance-between" key dancer ". In the design space can be understood from the symmetry of asymmetry, line design, floor design, top design, three-dimensional design and stage space. The results of the study of the concept of dancers and spatial design in dance Reflect on me Is Movement as a whole the form of this work can be studied through the theory and can be fully explained. In understanding the two concepts can be separated to then assembled intact in understanding it. This means that when reviewing the concept of dancers and spatial designs can be separated according to the sub-focus then in order to be fully understood then the parts of the study are put together so that they can easily understand the dance work Keywords— The concept of dancer, Space Design, My Reflection Is Motion